Incidencia del control interno en la gestión municipal de la municipalidad Distrital de Víctor Larco Herrera de Trujillo, año 2016. - Vasquez Llamo, Carlos Enrique (2019)
ABSTRACT The purpose of the present investigation was to determine the incidence of Internal Control in the Management of the District Municipality of Víctor Larco Herrera de Trujillo - year 2016. The design is a cross-sectional causal correlation study, since it seeks to establish the incidence of variables measured in a shows, in a single moment of time. The population consisted of 135 officials and 100 employees of the District Municipality of Víctor Larco. The sample was determined by non-probabilistic statistical sampling. The data collection was used the survey and the instrument was the questionnaire. The analysis of the information was made using descriptive and inferential statistics, as tools for the processing of the data was used statistical program SPSS, version 23 The results obtained have made it possible to verify that there is a significant incidence between the internal control and the municipal management of the district municipality of Víctor Larco, 2016, by means of the chi-square statistical test, with a level of significance of 0.05%. It is recommended to implement the institutional control body in accordance with the provisions of Law N ° 27785 Organic Law of the National Control System and the Office of the Comptroller General of the Republic.